Hsa_circ_0003204 Knockdown Weakens Ox-LDL-Induced Cell Injury by Regulating miR-188-3p/TRPC6 Axis in Human Carotid Artery Endothelial Cells and THP-1 Cells - Peng, Wenjia; Li, Shuai; Chen, Shiyue; Yang, Jiacheng; Sun, Ze (Frontiers in Cardiovascular Medicine, 2021)
Background: Circular RNAs (circRNAs) are involved in atherosclerosis (AS) development. However, the function and mechanism of circRNA hsa_circ_0003204 (circ_0003204) in carotid artery AS remain unclear. Methods: Oxidized low-density lipoprotein (ox-LDL)-treated human carotid artery endothelial cells (HCtAEC) and THP-1 cells were used as cell models of carotid artery AS. Relative levels of circ_0003204, microRNA-188-3p (miR-188-3p), and transient receptor potential canonical channel 6 (TRPC6) were detected by quantitative reverse transcription-polymerase chain reaction or western blot. The targeting relationship between circ_0003204 or TRPC6 and miR-188-3p and was assessed via dual-luciferase reporter analysis and RNA immunoprecipitation. Cell proliferation was assessed via 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2-H-tetrazolium bromide assay and 5-ethynyl-2’-deoxyuridine (EdU) assay. Cell apoptosis was analyzed via assessing cell caspase-3 activity, apoptosis, and apoptosis-related protein. Inflammatory response was analyzed via analysis of interleukin-1β (IL-1β), IL-6, and tumor necrosis factor-α (TNF-α). Oxidative stress was assessed via determination of reactive oxygen species (ROS), malondialdehyde (MDA), and superoxide dismutase (SOD). Results: circ_0003204 and TRPC6 levels were elevated and miR-188-3p expression was declined in ox-LDL-treated HCtAEC and THP-1 cells. circ_0003204 could regulate TRPC6 expression via mediating miR-188-3p. circ_0003204 silencing weakened ox-LDL-induced viability inhibition and apoptosis in HCtAEC cells and inflammatory response and oxidative stress in THP-1 cells via regulating miR-188-3p. miR-188-3p overexpression attenuated ox-LDL-induced injury in HCtAEC and THP-1 cells by targeting TRPC6. Conclusion: circ_0003204 knockdown mitigated ox-LDL-induced injury in HCtAEC and THP-1 cells via regulating the miR-188-3p/TRPC6 axis, indicating circ_0003204 might play important role in carotid artery AS.